Experimental investigation into the effects of composition and microstructure on the tensile properties and failure characteristics of different gypsum rocks - Hongfa Ma (Nature Portfolio, 2021)
Abstract The present work investigated the differences in the composition and internal microstructure of four types gypsum rock—fiber gypsum, transparent gypsum, alabaster, and ordinary gypsum by X-ray fluorescence spectrometry, X-ray diffraction, scanning electron microscope and Brazilian split test, and analyzed its effects on the tensile strength and fracture characteristics of gypsum rock. For alabaster, fiber gypsum, transparent gypsum, and ordinary gypsum, CaSO4·2H2O is the main component with 72.78%, 72.72%, 72.57%, and 71.51% content, and tensile strength of 1.79, 2.22, 3.22, and 4.35 MPa, respectively. In addition, the fracture line is arc-shaped, vertical, and zigzag for fiber gypsum, ordinary and transparent gypsums, and alabaster, respectively. On the microscopic level, fiber gypsum has an evident striated structure while the gradual increased pore development for alabaster, transparent gypsum, and ordinary gypsum. Gypsum rock has an obvious layered crystal structure with the increase of CaSO4·2H2O, contributing to the phenomenon with a larger grain size and lower tensile strength. In addition, the number of particles for alabaster, transparent gypsum, and ordinary gypsum increased in turn, while their particle size decreased uniformly, indicating that the lower CaSO4·2H2O content, the more sufficient energy accumulation and release. This paper can provide a theoretical basis for the analysis of the mechanical properties of rocks with different mineral composition and contribute to the design for different ore grades mining.